The Rights to Marry and Divorce: A New Look at Some Unanswered Questions - Cathy J. Jones (Washington University Law Quarterly, 1985)
Part I of the Article explores the status of marriage as a "fundamental" right. Part II examines the standard used by the Zablocki Court to invalidate the Wisconsin statute. Part II also addresses the issues of whether the Court applied an appropriate standard in reviewing the statute and whether Zablocki and subsequent cases should be addressed as due process rather than as equal protection cases. Part III sets forth some of the traditional restrictions states have placed on individuals' decisions to marry (for example, age, mental competence, incest) and some more modem restrictions (such as tax laws, nepotism rules and prison marriage rules) that may be included within the Zablocki approach, and discusses whether these restrictions must now fall as unconstitutional restraints on the fundamental right to marry. Part IV extends the right to marry into the realm of divorce and analyzes whether the two rights are in fact opposites and whether the decision in Zablocki should signal a new approach to state restrictions on divorce.
Keywords: Constitutional law – United States; Divorce; Separation (Law); Marriage